Peran Orangtua dan Penggunaan Gadget pada Anak Usia Sekolah - Ishariani, Linda; Taukhid, Muhammad (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2026)
Gadgets are interesting and inseparable from children's lives, leading to an increase in gadget use among children each year, which can impact their growth and development. Parental role significantly influences children's use of gadgets. The research aims to determine the relationship between parental roles and gadget use in school-aged children. The research design was correlational with a cross-sectional approach, using a sample of 26 respondents from a population of 120, selected by a purposive sampling technique. Data was collected using a questionnaire instrument and analyzed by Spearman's rho test. The study showed that parental roles were mostly good (61.5%) and gadget use by children was mostly high (69.2%). The results of the Spearman's rho test showed that p-value = 0.684 (α<0.05). It was concluded that no relationship between parental roles and gadget use in children. Gadget usage is not influenced by parental roles only, but also by environmental factors such as peer pressure. Parents are advised always to accompany, supervise, and be good role models for their children.